Immunohistochemical study of cyclooxygenase-2 in skin tumors. (October 2014) - Amirnia, Mehdi; Babaie-ghazani, Arash; Fakhrjou, Ashraf; Khodaeiani, Effat; Alikhah, Hossein; Naghavi-behzad, Mohammad; Zarrintan, Armin
Abstract Introduction: Anti-cancerous effects of cyclooxygenase-2 (COX-2) inhibitors have been reported in different cancers. High expression of COX-2 has been demonstrated in various neoplasms such as colorectal, gastric, esophageal, breast, non-small cell lung cancers, and pre-neoplastic lesions such as colorectal adenomas and Barrett's esophagus. Goal: The purpose of this study was to investigate percentage of positive COX-2 expression in skin tumors, including pre-malignant and malignant tumors. Methods: This is an analytic cross-sectional study that includes 62 skin tumor samples, among which 49 samples were malignant and 13 were pre-malignant. After study for determination of pathologic kind of tumors, samples underwent immunohistochemical study for COX-2 expression. The DakoCytomation EnVision+System-HRP is a two-step extremely sensitive IHC staining technique which we used in this study. Results: Among the skin tumors, a considerable number of COX-2 expression were found in squamous cell carcinomas (SCC) (16 of 17; 94%), basal cell carcinomas (BCC) (28 of 32; 87.5%), Bowen's disease (BD) (8 of 9; 89%), and actinic keratosis (AK) (4 of 4; 100%). Conclusion: COX-2 expression was positive in skin tumors including malignant and pre-malignant skin lesions. This study strongly suggests that COX-2 can be one of the molecular targets in treating various skin tumors.